Strategic Development of Community-Based Tourism Entrepreneurship in Volcanic Ecotourism Destinations - Triwahyuningsih, Nike; Kusmiyarti, Tati Budi; Noviastuti, Nina (Universitas Negeri Makassar, 2026)
This study aims to formulate strategic directions for the development of community-based tourism entrepreneurship in a volcanic ecotourism destination by examining its internal and external conditions. The analysis employed the Internal Factors Analysis Summary, External Factors Analysis Summary, and SWOT framework to identify the main strategic priorities for sustainable destination development. Secondary data derived from visitor perceptions and management assessments were used to evaluate the destination’s strengths, weaknesses, opportunities, and threats. The findings indicate that internal strengths, particularly the attractiveness of the volcanic landscape and strong community participation, slightly outweigh existing limitations such as inadequate amenities and limited accommodation capacity. The external environment is also relatively favorable, supported by increasing demand for nature-based tourism and educational tourism activities, although challenges remain in the form of volcanic hazards and potential environmental degradation. The integration of IFAS, EFAS, and SWOT results highlights several strategic priorities, including geotourism development, community-based homestay expansion, hazard mitigation systems, and infrastructure improvement. This study contributes a context-sensitive strategic framework that integrates conservation, disaster risk awareness, and local entrepreneurship within community-based tourism development. The findings provide practical implications for policymakers, destination managers, and local communities in promoting sustainable ecotourism development in environmentally sensitive tourism areas.